Effects of Cyclical Climate Change on Water Temperature Characteristics of Permafrost Slopes - Feike Duan; Lei Quan; Haowu Wang; Bo Tian (Applied Sciences)
Under the action of freeze–thaw cycles, the internal temperature and water distribution of slope soils in cold regions change significantly, which directly affects the stability of slopes. In order to study the differences in hydrothermal reactions at different depths and their impacts on the stability of slopes. This study establishes both a freeze–thaw model and a hydrothermal coupling model, combining field measurements with numerical simulations to examine the dynamic changes in hydrothermal characteristics within the slope. The results indicate that the variation in slope temperature with depth can be divided into three stages: initial freezing, stable freezing, and thawing. In the freezing stage, the negative temperature gradient drives water to migrate towards the freezing front, forming segregated ice and inducing frost heave. In the thawing stage, the latent heat released by the phase change in segregated ice promotes water to move towards the slope toe, increasing the water content there and indirectly exacerbating the risk of slope instability. The heat and moisture transfer in frozen soil slopes shows non-linear and dynamic characteristics. The unique process of one-way freezing and two-way thawing makes the thawing rate 1.35 times that of the freezing rate, and this asymmetric characteristic is the key to understanding the mechanism of slope instability.